2019
DOI: 10.24853/elif.1.2.95-106
|View full text |Cite
|
Sign up to set email alerts
|

Common Listening Challenges: Indonesian EFL Learners’ Perception

Abstract: Being a major part of internationalizing higher education, teaching English taps particular general cognitive abilities. It is mainly regarding listening that is hypothesized to have a higher influence on acquisition of foreign language. The aim of this study was to identify the common listening challenges experienced by Indonesian EFL learners. This research was practical research using descriptive methods of quantitative research. Subject of the study were subsequently randomly chosen, in which EFL learners … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
5
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 0 publications
1
5
0
2
Order By: Relevance
“…The research on listening anxiety, however, is still limited (i.e. Izzah & Keeya, 2019;Male, 2018) . Male (2018) using FLCAS investigated all four-skills language anxiety.…”
Section: E-issn 2541-0075 13mentioning
confidence: 99%
See 1 more Smart Citation
“…The research on listening anxiety, however, is still limited (i.e. Izzah & Keeya, 2019;Male, 2018) . Male (2018) using FLCAS investigated all four-skills language anxiety.…”
Section: E-issn 2541-0075 13mentioning
confidence: 99%
“…In listening anxiety particularly, he found that Indonesian university students learning English experience listening anxiety, especially when they could not understand the words or when they have to hear a longer text. A recent research on listening anxiety in academic listening class of Indonesian university students learning foreign language shows that high numbers of students experience listening anxiety due to inadequate listening proficiency and lexical resources, inability to deal with rapid speech rate and difficulty in identifying sound and phonemes (Izzah & Keeya, 2019).…”
Section: E-issn 2541-0075 13mentioning
confidence: 99%
“…Those three difficulties are pronunciation, personal characteristics, and content. Izzah & Keeya (2019) find that distortions, vocabularies, phonology, passage complexity, and the speech rate are the common difficulties for students in listening class due to the variety in pronunciation, individual characteristics, and content.…”
Section: Introductionmentioning
confidence: 96%
“…Like speaking, listening skills are greatly desired, yet also perceived as among the most challenging communication skills by most ESL learners [13]. Generally, an average individual spends approximately forty-five percent of their normal daily lifetime [14].…”
Section: Introductionmentioning
confidence: 99%